Factors Affecting Consumer Taste in Determining the Type of Drink Agades.id Labuhanbatu - Nasution, Andre Agasi Pratama; Parlaungan, Ade; Rambe, Bhakti Helvi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The progress of a food and beverage product business can be noticed through its advertisements because by advertising its products, people will recognize it. Brand image also supports the success of a business, because a brand that is known to the wider community will influence consumer desires. Lastly is product design, where the form of packaging also influences consumer tastes from AGADES.ID, especially ZOZU products. Based on the results of the analysis and discussion that has been carried out, it can be concluded that the partial hypothesis testing shows that the advertising variable has a positive and significant effect on the consumer’s taste variable, the brand image variable has a positive and significant effect on the consumer's taste variable and the product design variable has a positive and significant effect on variable consumer tastes. This result means that the variable consumer taste can be influenced by advertising, brand image, and product design variables by 30.4%, while the remaining 69.6% is influenced by other factors not discussed in this study, such as discipline, motivation, and so forth.